Utilization of coconut residue in chocolate coated confections - Liao, Christine V.
Chocolate coated confections utilizing formulated coconut residue as center were produced. The effects of center type used (caramel and cream paste) and sugar to sapal ration (3:4, 2:4 and 1:4) on consumer acceptability of the products were studied. Appearance, sweetness, coconut flavor, chocolate flavor, mouthfeel and overall acceptability were evaluated by 24 consumer panelists using nine-point hedonic scales. Water activity and moisture content determinations were likewise conducted. A two-month shelf life stability (in terms of microbial load and acceptability to consumers) was done also on the products stored at 18-25°C. Results were analyzed using analysis of variance and mean computation. Results indicated that all samples were acceptable to consumers although the caramel-centered products received higher scores. The caramel-centered chocolates registered lower activities and were found acceptable to consumers for three weeks when stored at 18-25°C. The cream paste-centered chocolates kept for less than two weeks at the same temperature of storage.